Kemampuan Literasi Matematis Siswa-Siswi Di Gorontalo - Kristiani Manik; Abdul Djabar Mohidin (Research in the Mathematical and Natural Sciences, 2024)
This study aims to determine the mathematical literacy abilities of students in Gorontalo. This study seeks to uncover and describe the problems of mathematical literacy faced by students. Literacy plays an important role for students. One of the literacy that must be mastered by students is mathematical literacy. Several mathematical literacy skills are widely reviewed in national articles. The research is more dominant in discussing the profile of students' mathematical literacy skills, the influence of learning models on mathematical literacy skills and the rest describes the results of a literature study on mathematical literacy with reference to nine article documents.